DDX3X mutations in two girls with a phenotype overlapping Toriello–Carey syndrome. Issue 5 (29th March 2017) - Dikow, Nicola; Granzow, Martin; Graul‐Neumann, Luitgard M.; Karch, Stephanie; Hinderhofer, Katrin; Paramasivam, Nagarajan; Behl, Laura‐Jane; Kaufmann, Lilian; Fischer, Christine; Evers, Christina; Schlesner, Matthias; Eils, Roland; et al.
Abstract : Recently, de novo heterozygous variants in DDX3X have been reported in about 1.5% of 2659 females with previously unexplained intellectual disability (ID). We report on the identification of DDX3X variants in two unrelated girls with clinical features of Toriello–Carey Syndrome (T‐CS). In patient 1, the recurrent variant c.1703C>T; p.(P568L) was identified when reconsidering X‐linked de novo heterozygous variants in exome sequencing data. In patient 2, the DDX3X variant c.1600C>G; p.(R534G) was also detected by exome sequencing. Based on these data, de novo heterozygous DDX3X variants should be considered not only in females with unexplained ID, but also in individuals with a clinical diagnosis of T‐CS.